The influence of LiH on the rehydrogenation behavior of halide free rare earth (RE) borohydrides (RE = Pr, Er) - Heere, M.; Payandeh GharibDoust, S.; Frommen, C.; Humphries, Terry; Ley, M.; Sørby, M.; Jensen, T.; Hauback, B. (R S C Publications, 2016)
© 2016 the Owner Societies. Rare earth (RE) metal borohydrides are receiving immense consideration as possible hydrogen storage materials and solid-state Li-ion conductors. In this study, halide free Er(BH4)3 and Pr(BH4)3 have been successfully synthesized for the first time by the combination of mechanochemical milling and/or wet chemistry. Rietveld refinement of Er(BH4)3 confirmed the formation of two different Er(BH4)3 polymorphs: a-Er(BH4)3 with space group Pa3, a = 10.76796(5) Å, and ß-Er(BH4)3 in Pm3m with a = 5.4664(1) Å. A variety of Pr(BH4)3 phases were found after extraction with diethyl ether: a-Pr(BH4)3 in Pa3 with a = 11.2465(1) Å, ß-Pr(BH4)3 in Pm3m with a = 5.716(2) Å and LiPr(BH4)3Cl in I43m, a = 11.5468(3) Å. Almost phase pure a-Pr(BH4)3 in Pa3 with a = 11.2473(2) Å was also synthesized. The thermal decomposition of Er(BH4)3 and Pr(BH4)3 proceeded without the formation of crystalline products. Rehydrogenation, as such, was not successful. However, addition of LiH promoted the rehydrogenation of RE hydride phases and LiBH4 from the decomposed RE(BH4)3 samples.